The Man and the Virtue of Humbleness. Orthopraxy as an effect of the Love of Creation (Environment) - Brînzea, Nicolae; Ciucă Bancu, Cosmin (Technium Social Sciences Journal, 2022)
Being created by God out of love, man, by the rationality with which he was endowed, understands how he must relate both to His Creator and to all created things, for although he is the crown of creation, that is, the one for whom they have all have been done, yet he cannot afford to destroy the environment of manifestation of the relationship between him and God.